Knowledge connectivity: An agenda for innovation research in international business - Cano-Kollmann, Marcelo; Cantwell, John; Hannigan, Thomas J; Mudambi, Ram; Song, Jaeyong (Journal of International Business Studies, 2016)
The innovation-driven multinational enterprise (MNE) has dominated international business (IB) research for several decades now. Beginning with the award-winning research of Dunning, there have been calls for IB researchers to rediscover the importance of locations. Recent work has emphasized that firms and locations co-evolve with one another, as knowledge is transferred and leveraged across space. Integrating insights from IB and economic geography, we propose a research agenda for IB scholarship on spatially dispersed yet connected innovation processes. This agenda is premised on the current reality of global value chains in which mobile (MNEs, people) and immobile (locations) factors interact. The research perspective suggested recognizes that locations are host to increasingly “fine-sliced” activities, whose nature and composition are continuously changed by MNE-driven innovation processes. As today’s specialized activities become tomorrow’s standardized ones, the shifting distribution of global value creation depends on the pattern of international knowledge connectivity.